ACERATHERIUM FROM THE DHOK PATHAN FORMATION OF THE MIDDLE SIWALIKS, PAKISTAN - M. A. Khan; A. M. Khan; U. Farooq; M. Iqbal; M. Akhtar (Journal of Animal and Plant Sciences, 2009)
Dental remains of the rhinoceroses comprising right and left fragmentary maxillae bear first, second and third molars are recovered from the Dhok Pathan Formation of the Middle Siwaliks. The remains are identified and assigned to Aceratherium sp. as well as these are compared with the other late Miocene rhinoceroses Aceratherium perimense, A. abeli, A. incisivum and Chilotherium intermedium. The findings allow discussion on the diversity of the late Miocene rhinoceroses.
Keywords: Rhinoceroses; Dhok Pathan; Aceratherium; Middle Siwaliks; Miocene